Lung cancer screening in the healthcare system of Bosnia and Herzegovina - Larisa Gavran; Gina Fatahi; Maja Račić (Medicinski glasnik, 2023)
Lung cancer incidence in Bosnia and Hercegovina is high. The implementation of evidence-based lung cancer screening based on low-dose computed tomography (LDCT) may detect lung cancer early and decrease mortality specific to lung cancer. However, LDCT receipt may be unsatisfactory in Europe due to a low distribution of scanners and radiologists or poor access to care. In this paper, we propose a framework for the implementation of lung cancer screening in primary healthcare of Bosnia and Herzegovina based on the United States Preventative Services Task Force recommendation from 2021 and the American College of Radiology Lung CT Screening Reporting & Data System from 2022.
Keywords: early detection of cancer; low -dose computed tomography; lung neoplasms